A ousadia como horizonte: religando vida e ideias na formação em enfermagem - Saraiva, Ana Karinne de Moura (2011)
A proposal of formation in health/nursing built on classic science, on reducing thought and flexnerian paradigm is insufficient to comprehend and intervening with an amplified way on health needs of population, given that it is produced by fragmentation of knowledge, rationalization of thought, mechanizing and biological attitudes. It is necessary that formation in health/nursing allows the construction of effectiveness of principles and guidelines of Unique System of Health (Sistema Único de Saúde - SUS). In this context of emergency of a complex formation in health/nursing, life trajectories and formation of the nurses: Abigail Moura, Francisca Valda and Raimunda Germano are examples of transgressor and successful experiences which allow inquietude, changing and transforming formation patterns and self-formation. The present study is built from the comprehension of method as strategy , defended by Morin and complexity sciences. Has as objects building biographies of formation of these three nurses who express a formation model more totalizing and humanitarian, analyzing and discussing starting from the three biographic fragments guiding principles for the current process of formation in health/nursing. From the biographies, the courage and humbleness emerge as landmarking principles of their experiences. Humbleness neither as self-depreciation nor humiliation but as consciousness of our uncompleted and unfinished essence, acceptance of boundaries and potential and reduction of intellectual vanity. Courage, for its part, is the human pulsing, uncertain for nature, which brings us to act, to face and persevere on moments of fear and difficulties. A formation in health and nursing based on courage and humbleness allows the subjects to be taken away from indifference, arrogance, inertia, pragmatism: bets on ethic and political subjects capable of minimizing unequal, inhumane and excluding processes. Na intellectual and Professional attitude which politizes the thought and science is what must be expected from a complex formation in health field, in latu mode on nursing, in particular